Investing in the high yield municipal market : how to profit from the current municipal credit crisis and earn attractive tax-exempt interest income - Nguyen, Triet, 1956- (Hoboken, N.J. : Wiley, 2012)
'A practical guide to profiting from the high yield municipal marketThis unique guide to the high yield municipal bond market sheds some much-needed light on this esoteric but profitable corner of the fixed-income world. It fills the void between the general reference handbooks on municipal bonds and the superficial treatment of do-it-yourself bond guides, with an emphasis on practical trading applications.Having witnessed the beginning of the modern high yield tax-exempt institutional market, author Triet Nguyen documents its historical evolution, outlines a conceptual framework for high yield tax-free investing, one that takes into account both interest rate and credit cycles, and reviews the latest historical data on municipal defaults, including for the first time the non-rated sector. Current distressed opportunities are also discussed. Along the way, Nguyen takes the time to discuss in detail the pros and cons of investing in pre-packaged high yield vehicles--from mutual funds to hedge funds to exchange-traded funds--with frank and objective insider tips on how these slickly marketed products really work. For the truly committed investor who wants to do his or her own homework, Nguyen and a group of industry experts go over the key investment considerations for several major classes of high yield tax-exempt bonds. Offers unique insights into the risk/return, trading, and liquidity characteristics of high yield municipal instruments Includes interesting case studies to fully illustrate the high yield investing process Written by an insider of both the asset management industry and the broker-dealer community Investing in the High Yield Municipal Market will put you in a better position to profit in this arena and help you excel in today's tough financial environment'--
Includes index.
Keywords: Municipal bonds -- United States; Government securities -- United States